RICE FARMERS' PERCEPTIONS ON THE PERFORMANCE OF AGRICULTURAL EXTENSIONS IN KEDUNGSUGO VILLAGE, PRAMBON DISTRICT, SIDOARJO REGENCY - Tama, Rivandy Aria; Soedarto, Teguh; Setiawan, Risqi Firdaus (Agridevina : Berkala Ilmiah Agribisnis, 2024)
Agricultural extension in Kedungsugo Village is carried out by an agricultural instructor using the extension method, namely face-to-face. The aim of this research is to determine the characteristics of rice farmers and determine rice farmers' perceptions of the performance of agricultural instructors in Kedungsugo Village, Prambon District, Sidoarjo Regency. The sampling method used in this research was simple random sampling with 34 rice farmers as respondents. The first and second objectives were analyzed descriptively. The results of the research show that 1) The characteristics of rice farmers in Kedungsugo Village, Prambon District, Sidoarjo Regency, the majority are male with an age range of 14 - 64 years with the highest level of education being elementary and middle school, with a level of farming experience of 20 - 35 years and extensive The most land cultivated is 0.5 -1 Ha. 2) Rice farmers' perceptions of the performance of agricultural instructors are included in the good category with an average score of 711.4 with an index of 83.62% in the good category. Where the highest score is in Increasing the Productivity of the Rice commodity agribusiness, namely with a total score of 723 with an index of 85% in the Very Good category and the lowest score is in the Agricultural Extension Program aspect with a total score of 683 with an index of 80.3% in the good category.Keywords: Perception of Rice Farmers, Agricultural Extension, Performance of Agricultural Extension